РОЗВИТОК СПРИТНОСТІ НА САМОСТІЙНИХ ЗАНЯТТЯХ (Педагогіка вищої та середньої школи, 2008)
The article deals with the methodical modes of development and perfection of students’ dexterity during independent training.